Analisis Hukum dan Budaya Catcalling pada Perempuan di Lingkungan Masyarakat - Zahra, Raisya Syafira; Anamy, Mulan Kasisty; Thalib, Sabrina Riyadh; Mulyana, Dian; Japono, Saskia Salsabila; Rahma, Deva Aurelia; Maulana, Rivo Denra; Gutama, Alma Florydia; Mulyadi, Raysha Aulia Fazila (IAI Nasional Laa Roiba Bogor, 2024)
Catcalling is a frequent phenomenon in society where a person verbally harasses or humiliates women in public spaces through sexual comments or unwanted behavior. It creates discomfort, anxiety and even trauma for victims, and reflects gender and power inequalities in our culture. A legal and cultural analysis of catcalling of women reveals the complexity of addressing this issue. While some jurisdictions have laws against verbal harassment, enforcement is often ineffective, and cultures that maintain gender stereotypes reinforce the behavior. The importance of education, public awareness and cultural change in combating catcalling is essential in creating a safer and more equal environment for women in society.